Do Mothers and Fathers Assess their Children's Behavioral Problems in the Same Way as do their Children? An IRT Investigation on the Strengths and Difficulties Questionnaire. (28th November 2019) - Iwata, Noboru; Kumagai, Ryuichi; Saeki, Izumi
Abstract: This study investigated the equivalence of different types of informants, such as children (or early adolescents) and parents, in evaluating child externalizing and internalizing problems. We applied a polytomous item response theory (IRT) model for the Strengths and Difficulties Questionnaire (SDQ). We obtained responses to three subscales—Conduct Problems, Hyperactivity/Inattention, and Emotional Symptoms—from 541 elementary school students aged 10–12 years, fathers for 233 students, mothers for 275 students, and the homeroom teachers for 524 students. Expected values on the individual item calculated by the discrimination and threshold parameters were compared among students, fathers, and mothers as an investigation of differential item functioning (DIF) or differential informant functioning. Assessing either externalizing or internalizing problems were mostly equivalent between fathers and mothers, and most items for externalizing problems functioned equally between students and parents, whereas items for internalizing problems showed DIF between them. IRT also yielded that the intervals of response categories varied across items, particularly for the conduct problems items "fight" and "steal, " and positively worded items showed an extremely low threshold.